Prevalence and associated factors of workplace violence against nurses in different-level hospitals: a cross-sectional study in Lanzhou, China - Wang, Fei; Wang, Jinyu; Li, Yuting; Liu, Wenjie; Li, Sheng (Frontiers in Public Health, 2025)
BackgroundWorkplace violence (WPV) is a severe challenge faced by healthcare systems globally, posing significant threats to the occupational safety and wellbeing of nursing staff. This study aims to understand the prevalence of WPV experienced by nursing personnel in different levels of hospitals in Lanzhou, China, analyze its key influencing factors, and explore the negative impact of WPV on the occupational wellbeing of nurses.MethodsThis study employed a cross-sectional survey design, conducted from February to March 2025, utilizing a multi-stage sampling method to survey nursing staff from five tertiary hospitals and five secondary hospitals in Lanzhou. A total of 1,702 valid questionnaires were collected. Data were gathered using the “Questionnaire on Workplace Violence Exposure Among Healthcare Workers” and the “Occupational Wellbeing Scale for Healthcare Workers.” Descriptive analysis, chi-square tests, Wilcoxon rank-sum tests, and multivariate logistic regression analysis were performed using SPSS 27.0.ResultsThe study found that the overall incidence rate of WPV among nursing staff in the past year was 69.92%, with verbal abuse being the most common form (69.04%). The incidence rate of WPV in tertiary hospitals (74.97%) was significantly higher than that in secondary hospitals (64.86%; P < 0.001). Multivariate logistic regression analysis indicated that hospital level, affiliation, department, education level, parental status, and years of service were independent influencing factors of WPV (P < 0.05). Nurses who experienced WPV scored significantly lower in all dimensions of occupational wellbeing (physical and mental health, value realization, social support, financial income, and work environment) compared to those who did not experience WPV (P < 0.001).ConclusionThe incidence rate of WPV among nursing staff in Lanzhou is at a high level and is closely related to hospital tier, department type, and individual characteristics. WPV significantly reduces the occupational wellbeing of nurses. The findings suggest that healthcare institutions should implement tiered and targeted intervention strategies, enhancing organizational support, optimizing violence prevention measures, and providing psychological interventions to effectively improve the occupational safety and wellbeing of nursing staff.